Beszélgetések a pszichoanalízisről 2/5 Ferenczi Sándor és a budapesti pszcihoanalízis
The most significant representative of Psychoanalysis in Budapest was the neurologist Sándor Ferenczi. He met Freud in 1908. Because he worked in a hospital, he met a large number of patients and his rich experience and exceptional personality had a decisive influence on Hungarian psychoanalysis. He had a lively relationship with the most prominent intellectuals of Hungary of that age, for example Gyula Krúdy, Frigyes Karinthy and Dezso Kosztolányi. He also had an impact on Mihály Babits's and László Nemeth's work. Although Ferenczi was one of Freud's most significant collaborators for 25 years, they put a different emphasis on various aspects of their work during their working lives. Ferenczi was primarily concerend with healing. In contrast to this, Freud concieved himself primarily as a scientist and a researcher. He did not want to find the cures for illnesses, he rather wanted to explore and understand them. It was no accident that Ferenczi was called "the expert of the hopeless cases". His devoted, understanding and generous behaviour as a doctor made him also famous among those psychologically ill patients whose chances of recovery had already been given up by other physicians. Ferenczi often refered to the capabilities psychoanalysis had in forming society and the importance of pedagogy. Not only the inner processes going on in people's mind captured his interest but also the relationship between the patient and the psychoanalyst. As opposed to Freud, who considered the analyst's neutral behaviour to be the pledge of psychoanalysis, Ferenczi rather believed in the healing power of a more active behaviour on the doctor's part. This was the fact in which he renewed psychoanalytic thinking. He was the founder of the Hungarian Psychoanalytic Association in 1913. Among his most significant students we can mention the name of Michael Balint, who from 1939 on continued his praxis in England and Imre Hermann who ensured the continuity of psychoanalysis in Hungary after the Second World War. An interesting and special representative of the so called Budapest School was Géza Róheim, who made his mark in the field of anthropology and psychoanalysis. In these conversations, we trace the history of the Budapest School. Péter Forgács